Crinitodiscus ozkani sp. n., a new uropodid mite from Turkey (Acari, Mesostigmata, Uropodidae) - Bal, Durmu‘ Al§ (Zootaxa, 2005)
The genus Crinitodiscus (Uropodidae) is re-described and its description supplemented with additional new data. A new species, Crinitodiscus ozkani sp. n., is described from specimens collected from the Black Sea region of Turkey. All life stages of the new species are described, and an identification key for the adults and nymphs of the four known species of Crinitodiscus is presented.